SUKUK, PERKEMBANGAN DAN IMPLEMENTASINYA DI INDONESIA DAN DAMPAKNYA TERHADAP PEREKONOMIAN - Komala, Adeh Ratna; Agnes Nabila, Sheyra; Fauziyah, Nisa; Andini, Nadia; Fahrezi, Abin; Ayu Pramesharry, Paradya (Jurnal Riset Akuntansi, 2025)
This research discusses the development of sukuk in Indonesia and its impact on the national economy. Retail Sukuk and Savings Sukuk are safe and affordable funding alternatives, with advantages such as safe investment, helping to build the country, halal, profitable, and affordable. The research method used is a qualitative descriptive study with a case study approach. Data was collected through a literature review that included official reports, scientific journals, and government documents related to Islamic finance and sukuk. Analyses were conducted to identify the development trend of sukuk, as well as the implementation of sukuk in investment practices and its impact on economic stability, the growth of the Islamic finance industry, and the management of the state budget deficit. The results showed that sukuk has a significant role in promoting economic growth, financial stability, and financial inclusion. In addition, sukuk issuance by the government and private sector continues to increase, supported by proactive government policies and high investor demand. The implementation of sukuk not only impacts the financial sector but also contributes positively to the overall development of the national economy. Keywords: Sukuk Development, Sukuk Implementation, Indonesian Economy.